LITHUANIA’S ACCESSION INTO THE EURO ZONE – ANALYSIS OF INSTITUTIONAL AND POLITICAL CHANGES IN LITHUANIA AND THE CHOICE OF THE TIMING - VILPIŠAUSKAS, RAMŪNAS (Politologija, 2015)
The article discusses Lithuania’s accession into the euro zone, first, by presenting the political economy analysis of the first unsuccessful attempt to introduce euro in 2007 and then comparing it with the second, successful attempt to do that in 2015. The focus is on legal, institutional and political changes, for example, the strengthening of non-majoritarian institutions, and the functional linkages between monetary policy and budgetary or regulatory policies. It is argued that although the existence of a currency board reduced uncertainty linked to the fluctuating exchange rate regime and facilitated the participation in the Exchange rate mechanism II, due to the lack of political consensus in the country and misaligned monetary and budgetary and regulatory policies, in particular as Parliamentary elections approached, the actual accession into the euro zone was achieved only ten years after joining the EU and Lithuania was the last of the three Baltic States to accomplish that. It should be noted that due to the different regimes of monetary and exchange rate policies in the three Baltic States, on the one hand, and Poland, on the other, for the former the euro introduction represented a final step out of the crisis of 2008–2009 while in the latter the experience of 2009 resulted in the indefinite postponement of this goal. According to the survey of political elites in Lithuania conducted for this project, the main motive for joining the euro zone is mostly linked to the perceived economic benefits, while the ‘seat at the table’, i.e., the possibility to participate in the decisionmaking of the euro zone and security benefits from being part of the core member states of the EU are less important.